Practice degree of Faculty Members at the Faculties of Economics in Benghazi and Omar Al-Mukhtar Universities for the Ethics of the University Education Profession from the student’s Point of View - إبراهيم حمد صباح; Abdulalim, Bakra (Dirasat in Economics and Business, 2024)
This study aims to identify practice degree of faculty members at the Faculties of Economics in Benghazi and Omar Al-Mukhtar Universities for the ethics of university education profession (personal dimension, university regulations and instructions, relationship with students, and teaching) from the student's point of view. In addition to revealing the significance of differences between the averages of responses of the study sample about the degree of practice of faculty members at the Faculties of Economics in Benghazi and Omar Al-Mukhtar Universities for the ethics of university education profession according to personal variables (gender, university, specialization). To achieve this, the study followed a descriptive-analytical approach and relied on the questionnaire as a tool for collecting study data. The study population consists of students expected to graduate for the fall 2022 semester, the number of them is (736) students, both male and female, at the faculties under study, A stratified random sample of (254) individuals was selected, and the questionnaire was distributed on the study sample. The study data was analyzed using the Statistical Package for the Social Sciences (SPSS). The study showed a number of results, including: the degree of practice of faculty members at the Faculties of Economics in Benghazi and Omar Al-Mukhtar Universities for the ethics of university education profession from the students' point of view was high on both total and dimensional levels, The results also show that there were significant differences between the averages of responses of the study sample about the degree of practice of faculty members at the Faculties of Economics in Benghazi and Omar Al-Mukhtar Universities for the ethics of university education profession due to gender variable and in favor of female students, while there are no significant differences due to the faculty and specialization variables. Finally, in light of the previous results, this study presented a number of recommendations.